Neural correlates of response inhibition in patients with bipolar disorder during acute versus remitted phase. (14th September 2019) - Kopf, Juliane; Glöckner, Stefan; Schecklmann, Martin; Dresler, Thomas; Plichta, Michael M.; Veeh, Julia; Kittel-Schneider, Sarah; Reif, Andreas
Abstract: Objectives: Elevated behavioural impulsivity has been shown to be a core feature of bipolar disorder. However, no study has so far investigated impulsivity-related brain activation in patients with BD during acute versus remitted phase. To address the question whether elevated behavioural impulsivity and its differential neural pathways is a state or trait marker of BD, we employed a combined stop signal-go/no-go task in 30 controls, and 37 depressed and 15 remitted patients who were retested. Methods: Frontal brain activation was recorded using near-infrared spectroscopy. Results: Behaviourally, we found increased impulsivity as indexed by higher stop signal reaction time for patients in their depressed phase while remitted patients did not differ from controls in any measure. In contrast, brain activation measurements revealed an opposite pattern: compared to controls, depressed patients did not show significant differences, while the remitted group displayed significantly decreased activation in bilateral prefrontal cortex during successful inhibition. Analysis of the remaining conditions (go, no-go, unsuccessful inhibition) did not reveal significant differences. Conclusions: Therefore, behavioural impulsivity and prefrontal hypoactivation do not seem to be a trait marker of BD. As only successful inhibition differentiated between groups, a specific dysfunction of this inhibitory process and its neural pathway may be postulated in BD.